A gait functional classification of adolescent idiopathic scoliosis (AIS) based on spatio-temporal parameters (STP) - Boulcourt, Sarah; Badel, Anne; Pionnier, Raphaël; Neder, Yamile; Ilharreborde, Brice; Simon, Anne-Laure (Gait & posture, 2023)
Therapeutic decisions for patients with adolescent idiopathic scoliosis (AIS) are mostly based on static measurements performed on two-dimensional standing full-spine radiographs. However, the trunk plays an essential role in the human locomotion, and the functional consequences during daily activities of this specific and common spinal deformity are not factored in. Does patients with AIS have specific gait patterns based on spatio-temporals parameters measurements ? 90 AIS patients (aged 10–18 years) with preoperative simplified gait analysis were retrospectively included for analysis between 2017 and 2020. Spatio-temporal parameters (STP) were measured on a 3-m baropodometric gaitway and included the measurement of 15 normalized gait parameters. A hierarchical cluster analysis was performed to identify group of patients based on the similarities of their gait patterns, and functional variables’ inter-group differences were also measured. The subject distribution was calculated to identify the structural characteristics of the subjects according to their gait patterns. Three gait patterns were identified. Cluster 1 (46%) was defined by asymmetry, Cluster 2 (16%) by instability, and Cluster 3 (36%) by variability. Each cluster was significantly different from the other ones on at least 6 different parameters (p < 0.05). Furthermore, each cluster was associated with one type of curve: Lenke 1 for Cluster 1 (57.5%), Lenke 6 for Cluster 2 (40%) and Lenke 5 for Cluster 3 (43.5%). Patients with severe AIS have a dynamic signature during gait identified on STP. Understanding consequences of this deformity on gait may be an interesting avenue to study the pathological mechanisms involved in their dynamic motor organization. Furthermore, these results might also be a first step to study the effectiveness of the different therapies. •First functional classification of AIS based on STP.•Three distinct gait patterns identified with AIS.•Each gait pattern was related to one specific structural deformity (Lenke).•A possible way to understand the dynamical motor organization in AIS.